An OSCE Evaluation Tool for the Assessment of Emergency Medicine Resident Progression Performance of ACGME Patient Case and Interpersonal Communication Milestones - Miriam Kulkarni (Journal of Education and Teaching in Emergency Medicine, 2018)
Audience: This curriculum is designed to provide a standardized assessment of Emergency Medicine resident performance of selected ACGME Patient Care and Interpersonal Communication Milestones in Emergency Medicine.